Pilot Validation Study for the Spanish-language CDI-2 among Adolescents from Puerto Rico (Revista Puertorriqueña de Psicologia, 2020)
The Children’s Depression Inventory-2 (CDI-2) was validated and standardized for US children. Although some data is available on its Spanish-language 12-item short form, the psychometric properties of the Spanish full-length form (28-item) are unknown. We examined the internal consistency (alpha coefficient) and concurrent validity of the Spanish-language CDI-2 among 51 Puerto Rican youth (aged 12-18 years), recruited from a public school, a private school, and a local church. Scores on the Reynolds Adolescent Depression Scale-2 (RADS-2) were used as concurrent validity criteria. We found alpha coefficients of .84, .74 and .76 for the Total, Emotional Problems, and Functional Problems scores, respectively. Corrected item-total correlations from .13 (Arguments with friends) to .69 (Feeling lonely) were observed. Reliability coefficients for subscales ranged from .58 (Interpersonal Problems) to .65 (Ineffectiveness and Negative Self-Esteem). CDI-2 and RADS-2 scores correlated .87. Correlations between RADS-2 scores and CDI-2 subscales ranged from .66 to .70 (p ≤ .001). Similar validity coefficients were found for the short form (α = .68). Our initial report on the Spanish full-length CDI-2 suggest that its psychometric properties with Puerto Rican adolescents may be similar to those of the original Spanish CDI and those reported for Hispanics using the English-language CDI-2.